Toxicological Analysis by Computational Assessment Tools of Herbal Medicine Compounds Urushiol II and Bhilawanol-B from Semecarpus Anacardium - K. Jyothi Prasad; Sivakumar. Vulava; Vijaya Chandra Reddy Konda; K.R. Subash (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Semecarpus anacardium used in many Indian folklore medicine as ‘Ballataka’ or ‘Bhilwa’. They are alsoknown to cause pathological conditions by the presence of toxic principles in nut and roots of plants and possiblepharmacokinetic and toxicological profiling of known toxic principles are explored by computational tools.Aims & Objectives: The aims of the study were to study toxicological active principle Urushiol II and Bhilawanol-Bby computational analysis and prediction tools.Materials & Methods: This study was investigated on web-based tools PubChem to extract the chemical structure,followed by authentication and validation with the chemical formula. The two-dimensional structures are furtherconverted to three-dimensional (3D) structure with ChemSketch software; the derived 3D structures are thenscreened for molecular properties followed by absorption, distribution, metabolism, elimination, and toxicitythrough admetSAR software. The reports are analyzed and predicted for pharmacokinetic and toxicity charactersof Urushiol II and Bhilawanol-B from S. anacardium.Results: The compounds screened Urushiol II and Bhilawanol-B from S. anacardium both had drug likeness scoreof MLOGP>4.15, the LD 50 values of urushiol II is comparatively more 4000 mg/kg/d than bhilawanol 2700mg/kg/d for rat oral route testing and positive predictive results for skin irritation and allergic dermatitis. Thegenotoxicity battery assay was negative for both Urushiol II and Bhilawanol-B.Conclusion: The computational analysis predicts the uroshiol II and bhilawanol-B present in S. anacardium belongsto class II Toxic hazard classification.